n-Butane, iso-Butane and 1-Butene Adsorption on Imidazolium-Based Ionic Liquids Studied with Molecular Beam Techniques - Winter, Leonhard; Bhuin, Radha Gobinda; Maier, Florian; Steinrück, Hans-Peter (Chemistry - A European Journal, 2021)
The interaction of molecules, especially hydrocarbons, at the gas/ionic liquid (IL) surface plays a crucial role in supported IL catalysis. The dynamics of this process is investigated by measuring the trapping probabilities of n-butane, iso-butane and 1-butene on a set of frozen 1-alkyl-3-methylimidazolium-based ILs [CnC1Im]X, where n=4, 8 and X−=Cl−, Br−, [PF6]− and [Tf2N]−. The decrease of the initial trapping probability with increasing surface temperature is used to determine the desorption energy of the hydrocarbons at the IL surfaces. It increases with increasing alkyl chain length n and decreasing anion size for the ILs studied. We attribute these effects to different degrees of alkyl chain surface enrichment, while interactions between the adsorbate and the anion do not play a significant role. The adsorption energy also depends on the adsorbing molecule: It decreases in the order n-butane>1-butene>iso-butane, which can be explained by different dispersion interactions.
CRIS-Team Scopus Importer:2021-10-08
Keywords: adsorption; catalysis; gas-surface dynamics; ionic liquids; molecular beam